Aadhaar-based Biometric Authentication for PDS and Food Security: Observations on Implementation in Jharkhand's Ranchi District. Issue 3 (December 2017) - Menon, Sneha
This article is an exploratory study into the implementation of Aadhaar-based biometric authentication (ABBA) in fair price shops in Ranchi district. In August 2016, only 52 per cent of ration card holding households in Ranchi successfully bought their ration. We find that the move to make ABBA compulsory for public distribution system (PDS) is a key contributor to this low transaction rate. The implementation of ABBA is rife with technical issues such as incomplete seeding of cardholder information, biometric failure and administrative gaps such as inadequate failure reporting and back-up systems. Through an empirical survey and secondary analysis of government data, we find that each of these prevent participants from purchasing their entitlements. Mandatory ABBA thus poses a possible threat to the food security of PDS-dependent households. ABBA has not fulfilled the potential for technology to bring transparency and efficiency into the PDS as it excessively prioritizes the prevention of identity fraud over other important issues, which could be addressed with improved technology such as quantity fraud and inventory management.